EXPLORING EDUCATION AS A TOOL FOR SUSTAINABLE DEVELOPMENT IN NIGERIA - Nnabuo, Peter O.M.; Asodike, Juliana D. (European Scientific Journal, ESJ, 2012)
The roles education and schooling play in contributing to sustainable development is the focal point of this paper. It is very necessary to give attention to ways of promoting sustainable development through means such as formal, non-formal, informal education and skill development for employability in the light of the present political and social realities.